The severity of duodeno‐esophageal reflux influences the development of different histological types of esophageal cancer in a rat model1. Issue 7 (3rd October 2012) - Miyashita, Tomoharu; Miwa, Koichi; Fujimura, Takashi; Ninomiya, Itasu; Fushida, Sachio; Shah, Furhawn A.; Harmon, John W.; Hattori, Takanori; Ohta, Tetsuo
Abstract The mechanism through which each histological type of carcinoma arises from the esophageal mucosa remains unknown. This study was designed to investigate whether there is an association between the severity of duodeno‐esophageal reflux and the histological type of esophageal cancer. A series of 120 male Fischer rats, weighing ∼180 g, were randomized to receive one of the following procedures: duodeno‐forestomach reflux (DFR) with reduced exposure to duodenal contents, duodeno‐esophageal reflux (DER) with increased exposure to duodenal contents and three control operations (DFR, DER control and sham). The reflux of bile was estimated with 99mTc‐PMT scintigraphy. All animals were fed a standard diet without carcinogen. The esophageal mucosa was assessed 50 weeks after surgery for carcinoma. The median scanned fraction rate of duodeno‐esophageal reflux was significantly lower for the rodents in the DFR group than those in the DER group. Five of 28 rodents in the DFR group and 17 of the 22 rodents in the DER group developed esophageal carcinoma. None of the controls developed carcinoma. The five rodents in the DFR group developed SCC. Of 22 esophageal carcinomas for the DER group, nine were SCC, 12 ADC and one was adenosquamous carcinoma. The fraction of esophageal SCC for the DFR group was significantly higher than that for the DER group, while the fraction of esophageal ADC for the DFR group was significantly lower than that for the DER group. These observations suggest that the severity of duodeno‐esophageal reflux in rodents is related to the development of different histological types of esophageal carcinoma.